2017
DOI: 10.3390/healthcare5010005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipid Biomarkers in Major Depression

Abstract: In the UK, the lifetime-documented prevalence of major depressive disorder (MDD) is currently 10%. Despite its increasing prevalence and devastating impact on quality of life, the pathophysiological mechanisms underpinning MDD remain to be fully elucidated. Current theories of neurobiological components remain incomplete and protein-centric, rendering pharmacological treatment options suboptimal. In this review, we highlight the pivotal role of lipids in intra- and inter-neuronal functioning, emphasising the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 150 publications
(169 reference statements)
1
88
0
Order By: Relevance
“…Engelberg 8 proposed that reduced peripheral cholesterol levels may contribute to a decrease in brain serotonin, and that low membrane cholesterol may reduce the number of serotonin receptors, leading to elevated suicidal risks. Subsequently, more clinical studies have been performed; however the results were mixed, with studies showing positive, inverse or non-significant associations [2][3][4]9 . A few meta-analyses have been performed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Engelberg 8 proposed that reduced peripheral cholesterol levels may contribute to a decrease in brain serotonin, and that low membrane cholesterol may reduce the number of serotonin receptors, leading to elevated suicidal risks. Subsequently, more clinical studies have been performed; however the results were mixed, with studies showing positive, inverse or non-significant associations [2][3][4]9 . A few meta-analyses have been performed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The hiSSB group tended to have higher levels of CRP, IL-18, and MCP-1, although the difference in these inflammatory markers between the loSSB and hiSSB groups was not significant. Given that low grade inflammation may play a role as both a cause and consequence of low HDL-C levels [47,48], and higher HDL-C levels may act as a buffer against low-grade inflammation [49][50][51], the lower levels of HDL-C observed in the hiSSB group may have been a consequence of proinflammatory factors modulated by a high sugar dietary pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[37] Total serum cholesterol is a peripheral biomarker in diagnosis and monitoring of psychiatric disorders. [38] It was commonly observed that in patients suffering from MDD, there was decreased total cholesterol when compared to healthy controls. [39,40] Studies also claimed a lack of significant association between low serum cholesterol and depression in elderly cohorts.…”
Section: Discussionmentioning
confidence: 99%